Opinion: Farmers may not be infected but are certainly affected - Kumar, Niraj; Kumar, Anjani (HT Media Ltd, 2020)
Strict measures of social distancing may be crucial to curb the spread of Covid-19, but ignoring the farm sector and farmers would be a grave mistake.